Graphitic N in nitrogen-Doped carbon promotes hydrogen peroxide synthesis from electrocatalytic oxygen reduction. (15th August 2020) - Zhang, Junyu; Zhang, Gong; Jin, Shengyao; Zhou, Yujun; Ji, Qinghua; Lan, Huachun; Liu, Huijuan; Qu, Jiuhui
Abstract: Electrocatalytic two-electron oxygen reduction reaction (2e − ORR) is a promising strategy to achieve hydrogen peroxide (H2 O2 ) production, which can replace the anthraquinone method in industrial processes. Nitrogen-doped carbon materials are active and selective electrocatalysts for 2e − ORR; however, it remains challenging to develop N-doped carbons for practical H2 O2 production and pinpoint the exact role of nitrogen functionalities. Here, we examine covalent organic framework-derived nitrogen-doped carbons with well-defined porous structure and tunable N species for electrocatalytic H2 O2 production. Electrochemical studies show their highest ORR activity and H2 O2 selectivity of up to 75% in alkaline electrolyte. Notably, chronoamperometric bulk electrolysis achieves an unprecedented carbon-catalyzed H2 O2 yield rate of 1286.9 mmol gcatalyst −1 h −1 and a faradaic efficiency of 69.8% at pH 13. X-ray photoelectron spectroscopy analysis combined with control experiments reveals that graphitic N is responsible for H2 O2 production from 2e − ORR on N-doped carbons. Our work provides insights into the rational development of heteroatom-doped carbon electrocatalysts for efficient H2 O2 generation. Graphical abstract: Image 1